Light-emitting diode technology in vitreoretinal surgery - Dithmar, Stefan; Höh, Alexandra E.; Amberger, Roman; Ruppenstein, Mira Katharina; Ach, Thomas (Retina, 2011)
Background: - Systems for vitreoretinal illumination during surgery usually consist of an external light source and a light fiber. We introduce a new illumination system for vitreoretinal surgery based on the light-emitting diode technology, with an embedded light source in the handle of the light fiber, making a separate light source unnecessary. - Methods: - A prototype of a new illumination system for vitreoretinal surgery (ocuLED; Geuder, Heidelberg, Germany) was tested. This system consists of a handle with a built-in light-emitting diode, supported by an external power source. The OcuLED was analyzed in regards to wavelength, maximum radiant power, and maximum irradiance and was compared with three commercially available vitreoretinal illumination systems. Furthermore, the first intraoperative application and handling were evaluated. - Results: - The ocuLED system works with a cool white or a neutral white light-emitting diode and is powered externally. The wavelength spectrum shows a maximum at 565 nm and a second peak at 455 nm. Compared with other light sources, the proportion of potentially harmful blue light is low. Maximum radiant power and irradiance are in line with xenon and mercury vapor light sources. The intrasurgical light is bright and offers good visibility. The handle of ocuLED is slightly wider than commonly used light fiber handles, which do not affect its use during surgery. - Conclusion: - Technical progress in light-emitting diode technology allows minimizing the equipment for vitreoretinal illumination. The OcuLED provides bright illumination without an external light source. Wavelength spectrum, maximum radiant power, and irradiance are safe from the risk of phototoxic damage. Intrasurgical handling is identical to conventional light fibers.